Highly Substituted Pyrroles by a Gold(I)-Catalyzed Tandem Reaction of 1-(1-Alkynyl)cyclopropyl Oxime Ethers with Nucleophiles - Zhang, Yanqing; Zhang, Junliang (Synlett, 2012)
A gold(I)-catalyzed tandem reaction of 1-(1-alkynyl) cyclopropyl oxime ethers with nucleophiles under mild conditions has been developed, which provides a facile access to highly substituted pyrroles in moderate to excellent yields.
Keywords: pyrroles; gold; nucleophiles; cyclization; cyclopropane